2013
DOI: 10.3402/jev.v2i0.22097
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal ITGA3 interferes with non‐cancerous prostate cell functions and is increased in urine exosomes of metastatic prostate cancer patients

Abstract: BackgroundCancer cells are able to change the protein expression and behavior of non-cancerous surrounding cells. Exosomes, secreted by prostate cancer (PCa) cells, may have a functional role in cancer metastasis and present a promising source for protein biomarkers. The aim of the present study was to identify which proteins in exosomes can influence non-cancerous cells, and to determine whether we can use urine exosomal proteins to identify high-risk PCa patients.MethodExosomes were isolated by ultracentrifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 39 publications
(52 reference statements)
4
96
0
Order By: Relevance
“…Finally, our study is the first to show that the ␣ v ␤ 6 integrin that is transferred between different subsets of PrCa cells is functional and promotes cell adhesion and migration on LAP-TGF␤ in an ␣ v ␤ 6 integrin-dependent manner. Previous studies have suggested but not proven, or excluded, that exosomal transfer of integrins, as well as of other molecules such as heparanase, promotes cell motility on ECM in recipient cells (29,39). In contrast, Lee et al (40) demonstrate that exosomes released from human macrophages negatively regulate endothelial cell migration, promoting the internalization and degradation of the ␤ 1 integrin subunit in the recipient cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, our study is the first to show that the ␣ v ␤ 6 integrin that is transferred between different subsets of PrCa cells is functional and promotes cell adhesion and migration on LAP-TGF␤ in an ␣ v ␤ 6 integrin-dependent manner. Previous studies have suggested but not proven, or excluded, that exosomal transfer of integrins, as well as of other molecules such as heparanase, promotes cell motility on ECM in recipient cells (29,39). In contrast, Lee et al (40) demonstrate that exosomes released from human macrophages negatively regulate endothelial cell migration, promoting the internalization and degradation of the ␤ 1 integrin subunit in the recipient cells.…”
Section: Discussionmentioning
confidence: 97%
“…Proteomic analysis has shown that ␣ 2 , ␣ 3 , ␣ 6 , ␤ 1 , and ␤ 4 integrin subunits are found in microvesicles from PrCa cells (28). In addition, a recent study has shown that the presence of the ␣ 3 integrin subunit in PrCa cell derived-exosomes interferes with non-cancerous prostate cell functions (29). Moreover, Clayton et al (30) have shown that B cell-derived exosomes express functional ␤ 1 and ␤ 2 integrins that are capable of mediating anchorage to the extracellular matrix (ECM).…”
mentioning
confidence: 99%
“…129 Other studies have also investigated the proteo mic cargo of prostate-derived extracellular vesicles from urine. [130][131][132][133] Increased levels of α1-integrin and β1-integrin were found in urine exosomes of patients with metastatic prostate cancer, compared with patients The flowchart shows a step-by-step process by which the profiling and discovery of exosomal cargo molecules could ultimately be translated into a clinically applicable biomarker signature. At each step defined goals and criteria must be met in order to proceed to the next level.…”
Section: Prostate Tissuesmentioning
confidence: 99%
“…163 with nonmetastatic disease or those with BPH. 130 Likewise, δ-catenin associated with extracellular vesicles has been found at high levels in urine, 131 whereas prostate-specific membrane antigen and prostate stem cell antigen have also been identified in urine-derived exosomes of patients with prostate cancer. 26,29,129 In addition to exosomal protein markers, some transcriptomic changes have also been identified, including those affecting the expression of TMPRSS2 and, of course, PCA3.…”
Section: Prostate Tissuesmentioning
confidence: 99%
“…EV release appears to be a general biological process, and EVs have been detected in biological fluids such as blood, breastmilk, saliva [55,56] and urine [57]. EVs can thus be recovered from biological fluids and cell cultures for monitoring of specific pathophysiological processes.…”
Section: Evs For Liquid Biopsy In Cancermentioning
confidence: 99%